Biogenic silver nanoparticles of Clinacanthus nutans as antioxidant with antimicrobial and cytotoxic effects - Hock, Ing Chiu; Che Mood, Che Nurul Azieyan; Mohamad Zain, Nur Nadhirah; Ramachandran, Muggundha Raoov; Yahaya, Noorfatimah; Nik Mohamed Kamal, Nik Nur Syazni; Wai, Hau Tung; Yong, Yoke Keong; Chee, Keong Lee; Lim, Vuanghao (Hindawi Publishing, 2021)
Silver nanoparticles (AgNPs) previously synthesised using leaf (AgNP-L) and stem (AgNP-S) extracts of Clinacanthus nutans (C. nutans) were tested to evaluate antimicrobial, antioxidant, and cytotoxicity activities. The AgNPs showed good inhibition against bacteria, but not fungi. The inhibition results showed the highest activity against Staphylococcus aureus (S. aureus) with 11.35 mm (AgNP-L) and 11.52 mm (AgNP-S), while the lowest inhibition was against Escherichia coli (E. coli) with 9.22 mm (AgNP-L) and 9.25 mm (AgNP-S) in the disc diffusion method. The same trend of results was noted in the well diffusion method. The IC50 of AgNP-L and AgNP-S in 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assays was 417.05 μg/mL and 434.60 μg/mL, as well as 304.31 μg/mL and 326.83 μg/mL, respectively. Ferric reducing power (FRAP) assay showed that AgNP-L [872.389 μmol/L Fe(II)] and AgNP-S [612.770 μmol/L Fe(II)] exhibited significantly ( < 0.05) greater antioxidant activities than leaf extract (CNL) [152.260 μmol/L Fe(II)] and stem extract (CNS) [110.445 μmol/L Fe(II)] of C. nutans. The AgNPs were also proven to possess cytotoxic effects on the breast (MCF-7), cervical (HeLa), and colon (HT-29) cancer cells in a dose-dependent manner. AgNP-S and AgNP-L showed significantly ( < 0.05) higher cytotoxicity against MCF-7 (117.43 μg/mL) and HT-29 (78.47 μg/mL), respectively. In conclusion, the biosynthesised AgNPs from aqueous extract leaves and stem of C. nutans have demonstrated promising potential towards antioxidant, antimicrobial, and cytotoxicity activities.